Permethrin Resistance and Alternative Therapies in Scabies : A Systematic Review - Asmaul Khusna; Dinna Devi; Heffi Anindya Putri (International Medical Journal Corp. Ltd, 2026)
Introduction: Scabies, caused by Sarcoptes scabiei var. hominis, affects over 200 million people globally, with permethrin 5% cream serving as first-line treatment for decades. However, emerging evidence suggests increasing permethrin treatment failures, raising concerns about resistance. This systematic review aims to synthesize evidence on permethrin resistance in scabies and evaluate the effectiveness and safety of alternative therapeutic options. Methods: A systematic review was conducted following PRISMA guidelines. We searched multiple databases for studies investigating permethrin resistance or alternative scabies treatments. Included studies comprised randomized controlled trials, cohort studies, case-control studies, case series (≥5 patients), systematic reviews, and meta-analyses reporting clinical outcomes in human patients with confirmed or clinically diagnosed scabies. A total of 144 studies met inclusion criteria and underwent data extraction for resistance evidence, alternative therapy details, comparative effectiveness, safety profiles, and clinical context. Results: Documented permethrin resistance demonstrated significant geographic heterogeneity, with European studies reporting cure rates as low as 27-31% compared to 73-96% in South Asian settings. Global treatment failure prevalence increased by 0.58% annually (95% CI not reported). Resistance mechanisms included voltage-gated sodium channel mutations and enhanced glutathione S-transferase activity. Alternative therapies showed variable effectiveness: two-dose oral ivermectin (200 μg/kg one week apart) achieved 78-100% cure versus 58% for single-dose (P=0.021); topical ivermectin 1% achieved 96-100% cure by four weeks; benzyl benzoate 25% showed 87% cure in some studies but caused burning in 24% of patients; sulfur preparations achieved 94.4-100% cure by four weeks with mild adverse effects. Combination permethrin-ivermectin therapy demonstrated superior efficacy (84.6% vs 67.5-70.7% for monotherapies, P<0.01). Mass drug administration with ivermectin reduced scabies prevalence by 79% (95% CI not reported). Discussion: The geographic disparity in permethrin efficacy likely reflects true biological resistance evolution in regions with prolonged permethrin use, rather than methodological artifacts. Alternative therapies, particularly two-dose oral ivermectin and topical ivermectin, demonstrate excellent effectiveness in permethrin-resistant cases. Treatment selection should consider resistance patterns, patient age, pregnancy status, and resource availability. Combination approaches may offer advantages in refractory cases. Conclusion: Permethrin resistance represents an emerging global challenge requiring revised treatment algorithms. Two-dose oral ivermectin (200 μg/kg one week apart) should be considered first-line in regions with documented resistance, while topical ivermectin offers advantages in young children. Future research should focus on standardized resistance surveillance, novel agents including moxidectin and spinosad, and implementation strategies for resistant populations.